Assessment of building structure opening for dwelling - Marziatulhikmah, Maslan (2010)
Building structure opening or indoor ventilation is one of the important requirements for building especially for low-cost housing. Low cost-housing is one of the residential areas in Malaysia where its residents are from lower income groups. Residential satisfaction is an important indicator of housing quality and condition, which affects individual's quality of life. The factors which determine their satisfactions are depend on the suitability building structure opening. The purpose of this study is to investigate the residents' satisfaction and improve the building , structure opning for low cost housing. A study carries out at residential area in Pahang, Kuala Lumpur, Perak and Negeri Sembilan. To identify the level of satisfaction among occupants, questionnaire forms were distributed to low cost-housing residents. The effectiveness of these designs will be assessed from the type of occupants,type of construction area, renovation and the frequency of mechanical equipment used. From the surveys and findings being carried out, it was found that 6% of the residents not comfortable with the ventilation, 29% are slightly comfortable and 65% comfortable. Several recommendations are stated to improve the level of ventilation. In general, there are two methods used to improve ventilation flow inside a building: mechanical ventilation and natural ventilation.